Odpowiedzi

2010-03-25T18:04:07+01:00
A) -7+3y+9+2y=3+5y
b) x-3x+2-2x-7=5-4x
c)-5x+4y-y-7x-9y=-13x-6y
d)4x+5-x-4+x-3x=x+1
e) 0,5 a - 2a +9 - 0,5a - 11,5= -2a +2.5
f) -14 k +9k -13+k +3+4k=10k-10
g)-3k+2m+5m-7+k-m=6m-7-2k
h)2x-4+3x-2=5x-6
i) x-3y- 2x+6y=-x+3y
j)2y- 5 - 3y-4-8y+9=-9y
Najlepsza Odpowiedź!
2010-03-25T18:11:27+01:00
A) -7+3y+9+2y=-2+5y
b) x-3x+2-2x-7=--4x-5
c) -5x+4y-y-7x-9y=-15x-4y
d) 4x+5-x-4+x-3x=x+1
e) 0,5 a - 2a +9 - 0,5a - 11,5 =-2a-2,5
f) -14 k +9k -13+k +3+4k=-13k-10
g) -3k+2m+5m-7+k-m=-2k6m-7
h) 2x-4+3x-2=5x-6
i) x-3y- 2x+6y=3x+3y
j) 2y- 5 - 3y-4-8y+9=-9y+4